IDENTIFIKASI POTENSI EKOWISATA DI KAMPUNG ONGGAYA DAN KELURAHAN SAMKAI KABUPATEN MERAUKE - Norce Mote; Siti Masiyah (AGRICOLA, 2016)
District of Merauke has a high potency to develop the tourism sectors. Development can be carried out in accordance with the potential tourism resources they had. This research was conducted during one month, in December 2015, located at Onggaya Village, Pantai Payum and Lampu Satu (Samkai Area). The objectives of this research was to identify the potential ecotourism of area at Onggaya and Samkai Area in the District of Merauke. The Survey method was used in this research, and the data were analyzed based on potential category like recreational coastal tourism and mangrove tourism. The index value of ecosystem suitability in Onggaya coastal is 78,50%, which means that area can be categorized as an area with the appropriate category of parole. Furthermore, ecotourism suitability index (IKW) in Payum and Gudang Arang is 61.50%, which means conditional appropriate. If seen from IKW results, it can be said that both of these areas have the potency to be develop. The conclusion of this research in Onggaya Village having a good potency to develop as ecotourism area, in the other side Payum (Samkai Area) dan Gudang Arang (Maro Area) both are having a good ecology potency but couldn’t be developed causing by burdened of ground proprietary rights.